Mechanical Loading of Cartilage Explants with Compression and Sliding Motion Modulates Gene Expression of Lubricin and Catabolic Enzymes - Schätti, Oliver R; Marková, Michala; Torzilli, Peter A; Gallo, Luigi M (Cartilage, 2015)
OBJECTIVE: Translation of the contact zone in articulating joints is an important component of joint kinematics, yet rarely investigated in a biological context. This study was designed to investigate how sliding contact areas affect cartilage mechanobiology. We hypothesized that higher sliding speeds would lead to increased extracellular matrix mechanical stress and the expression of catabolic genes. DESIGN: A cylindrical Teflon indenter was used to apply 50 or 100 N normal forces at 10, 40, or 70 mm/s sliding speed. Mechanical parameters were correlated with gene expressions using a multiple linear regression model. RESULTS: In both loading groups there was no significant effect of sliding speed on any of the mechanical parameters (strain, stress, modulus, tangential force). However, an increase in vertical force (from 50 to 100 N) led to a significant increase in extracellular matrix strain and stress. For 100 N, significant correlations between gene expression and mechanical parameters were found for TIMP-3 (r(2) = 0.89), ADAMTS-5 (r(2) = 0.73), and lubricin (r(2) = 0.73). CONCLUSIONS: The sliding speeds applied do not have an effect on the mechanical response of the cartilage, this could be explained by a partial attainment of the "elastic limit" at and above a sliding speed of 10 mm/s. Nevertheless, we still found a relationship between sliding speed and gene expression when the tissue was loaded with 100 N normal force. Thus despite the absence of speed-dependent mechanical changes (strain, stress, modulus, tangential force), the sliding speed had an influence on gene expression.